Functional molecular markers for crop improvement. (2nd September 2016) - Kage, Udaykumar; Kumar, Arun; Dhokane, Dhananjay; Karre, Shailesh; Kushalappa, Ajjamada C.
Abstract: A tremendous decline in cultivable land and resources and a huge increase in food demand calls for immediate attention to crop improvement. Though molecular plant breeding serves as a viable solution and is considered as "foundation for twenty-first century crop improvement", a major stumbling block for crop improvement is the availability of a limited functional gene pool for cereal crops. Advancement in the next generation sequencing (NGS) technologies integrated with tools like metabolomics, proteomics and association mapping studies have facilitated the identification of candidate genes, their allelic variants and opened new avenues to accelerate crop improvement through development and use of functional molecular markers (FMMs). The FMMs are developed from the sequence polymorphisms present within functional gene(s) which are associated with phenotypic trait variations. Since FMMs obviate the problems associated with random DNA markers, these are considered as "the holy grail" of plant breeders who employ targeted marker assisted selections (MAS) for crop improvement. This review article attempts to consider the current resources and novel methods such as metabolomics, proteomics and association studies for the identification of candidate genes and their validation through virus-induced gene silencing (VIGS) for the development of FMMs. A number of examples where the FMMs have been developed and used for the improvement of cereal crops for agronomic, food quality, disease resistance and abiotic stress tolerance traits have been considered.